DETERMINANT OF TURNOVER INTENTION OF EMPLOYEES WITH WORK ENVIRONMENT AS THE INTERVENING VARIABLE - Usmar, Usmar; Anwar, M.; Setyowulan, Endang Sarwiningsih; Judijanto, Loso; Tawil, Muhamad Risal (International Journal of Artificial Intelligence Research, 2024)
An organization’s incapacity to keep workers may contribute to high level of turnover intention, which will be detrimental to the business. Good employees who are not given the opportunity to progress in the company cause employees to resign from their jobs.This study aims to analyze and examine the influence of transformational leadership, career development and job satisfaction on turnover intention with work environment as an intervening variable at Sinar Bahagia, East Lombok. Regression analysis and quantitative methods are used in this research. The data was collected using questionnaires distributed to all employees Sinar Bahagia. The sampling method used is census sampling technique with a total population of 55 employees. The data analysis with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study indicate that the transformational leadership, career development and job satisfaction have a significant effect on turnover intention, while work environment not have a significant effect on turnover intention at Sinar Bahagia. The work environment is proven to be able mediate the influence of transformational leadership and job satisfaction on turnover intention. While, work environment is unable to mediate the influence of career development on turnover intentionat Sinar Bahagia. The findings of this study can be reference uses as reference for future researchers who will study similar problems